2013
DOI: 10.2478/s13382-013-0126-y
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work characteristics and occupational co-exposures in industrial plants in Łódź, Poland

Abstract: Objectives: Night shift work involving circadian rhythm disruption has been classified by IARC as a probably carcinogenic to humans (Group 2A). Little is known about co-exposures of the night shift work in occupational settings. The aim of our study was to characterize night shift work systems and industrial exposures occurring in the manufacturing plants in Łódź, Poland, where night shift work system operates, with particular focus on potential carcinogens. Material and Methods: Data on the night shift work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Of importance here is that nurses in Poland work rotating system, mostly with 12 h long two shifts, while at industry the most prevalent system that includes three shifts, with five consecutive shifts (Peplonska et al, 2013), and thus consequences to lifestyle may differ. Given cross-national social and lifestyle differences, the limitation may also apply to generalization of the results to nurses in other countries, in particular, if their system of work is different.…”
Section: Discussionmentioning
confidence: 99%
“…Of importance here is that nurses in Poland work rotating system, mostly with 12 h long two shifts, while at industry the most prevalent system that includes three shifts, with five consecutive shifts (Peplonska et al, 2013), and thus consequences to lifestyle may differ. Given cross-national social and lifestyle differences, the limitation may also apply to generalization of the results to nurses in other countries, in particular, if their system of work is different.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the meta-analysis provided a meta-OR for eight studies that provide very different definitions and assessments of night shift work across studies. Moreover, only three studies of eight were of high quality according to the Newcastle- Ottawa Scale criteria (45). Out of those eight studies, four were included in Sigurdardottir's review (27)(28)(29)(30) and four are part of ours (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Among the five more recent studies included in our review, two were suggestive of an association between night shift work and prostate cancer (31,32) while three studies did not (33)(34)(35). Even though those five studies presented several positive features that should be emphasized: high quality exposure information with detailed lifetime job histories, large population size studies, information on sleep patterns, and chronotype in two studies of five, several limitations to an overall interpretation should also be highlighted: lack of standardization in both definition of night shift work and exposure assessment; different potential confounding factors taken into account; different prostate cancer outcomes either incidence or mortality; differences in populations studied some of them being population-based while others focused on specific occupational groups; few studies with information on prostate cancer aggressiveness, and few studies taking into account other occupational exposures that may also play a role in prostate cancer (45).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in France found that night‐shift workers were more frequently exposed to at least one carcinogen, or mutagenic and reprotoxic chemical and had a higher exposure intensity compared to occupations without night‐shift work . A study in industrial plants in Poland where a night shift work system operates found co‐exposure to other occupational hazards among workers including carcinogens to be relatively common …”
Section: Discussionmentioning
confidence: 98%